The Children’s Data Network: Harnessing the Scientific Potential of Linked, Administrative Data to Inform Children’s Programs and Policies - Foust, Regan; Hoonhout, Jonathan; Eastman, Andrea; Prindle, John; Rebbe, Rebecca; Nghiem, Huy; Suthar, Himal; Cuccaro-Alamin, Stephanie; Mitchell, Michael; Dawson, William; Palmer, Lindsey; Raj, Siddharth; et al. (International Journal of Population Data Science, 2022)
The Children's Data Network (CDN) is a data and research collaborative focused on the linkage and analysis of administrative records. In partnership with public agencies, philanthropic funders, affiliated researchers, and community stakeholders, we seek to generate knowledge and advance evidence-rich policies that improve the health, safety, and well-being of the children of California. Given our experience negotiating access to and working with existing administrative data (and importantly, data stewards), the CDN has demonstrated its ability to perform cost-effective and rigorous record linkage, answer time-sensitive policy- and program-related questions, and build the public sector's capacity to do the same. Owing to steadfast and generous infrastructure and project support, close collaboration with public partners, and strategic analyses and engagements, the CDN has promoted a person-level and longitudinal understanding of children and families in California and in so doing, informed policy and program development nationwide. We sincerely hope that our experience—and lessons learned—can advance and inform work in other fields and jurisdictions.